Axial concentration profiles and N2O flue gas in a pilot scale bubbling fluidised bed coal combustor - Tarelho, Luís António da Cruz
Atmospheric Bubbling Fluidised Bed Coal Combustion (ABFBCC) of a bituminous coal and anthracite with particle diameters in the range 500–4000 μm was investigated in a pilot-plant facility (circular section with 0.25 m internal diameter and 3 m height). The experiments were conducted at steady-state conditions using three excess air levels (10%, 25% and 50%) and bed temperatures in the 750–900 °C range. Combustion air was staged, with primary air accounting for 100%, 80% and 60% of total combustion air. For both types of coal, virtually no N2O was found in significant amounts inside the bed. However, just above the bed-freeboard interface, the N2O concentration increased monotonically along the freeboard and towards the exit flue. The N2O concentrations in the reactor ranged between 0–90 ppm during bituminous coal combustion and 0–30 ppm for anthracite. For both coals, the lowest values occurred at the higher bed temperature (900 °C) with low excess air (10%) and high air staging (60% primary air), whereas the highest occurred at the lower bed temperature (750 °C for bituminous, 825 °C for anthracite) with high excess air (50%) and single stage combustion. Most of the observed results could be qualitatively interpreted in terms of a set of homogeneous and heterogeneous reactions, where catalytic surfaces (such as char, sand and coal ash) can play an important role in the formation and destruction of N2O and its precursors (such as HCN, NH3 and HCNO) by free radicals (O, H, OH) and reducing species (H2, CO, HCs).